Effectiveness Of LKPD Containing Character Education Based On Group Investigation In Mathematics Learning - Hesti Noviyana; Joko Sutrisno AB (Jurnal Inovasi Matematika, 2025)
This study aims to examine the effectiveness of the use of LKPD containing Character education based on Group Investigation in mathematics learning in terms of student learning outcomes. The study is a quasi-experimental study with a pretest-posttest control group design. In this design, two groups of students (experimental group and control group) were measured for their learning outcomes on flat shape material, before and after treatment was given. The study population was grade VII students of SMP Negeri 7 Bandar Lampung. Data analysis of the results of this study used the t-test, with analysis prerequisites in the form of normality and homogeneity of variance tests. The results of the normality test with Kolmogorov-Smirnov showed a p value = 0.200 which is greater than 0.05, meaning that the data is normally distributed and the results of the homogeneity test with Levene's Test obtained a p value = 0.711 greater than 0.05, which means that the variance between groups is homogeneous. The results of the independent t-test for the comparison between the experimental group and the control group on the posttest using SPSS showed that the p-value = 0.000 which is smaller than 0.05, meaning that there is a significant difference between the mathematics learning outcomes of students in the experimental group using LKPD containing Character education based on Group Investigation and the control group. The average mathematics learning outcomes of the experimental group were 85, while the control group was only 74. This shows that the use of LKPD containing Character education based on Group Investigation is effective in mathematics learning in terms of students' mathematics learning outcomes on flat shape material.